2023
DOI: 10.36347/sasjm.2023.v09i06.009
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in the Elderly: Epidemiological, Clinical and Etiological Aspects in Internal Medicine at the Point "G" University Hospital

Abstract: Introduction: Anaemia is a condition that is often underestimated and insufficiently treated in the elderly. It is the most common haematological problem in this age group, with 30% of aetiologies remaining unexplained. In our context, few patients benefit from investigation, hence this study to assess the state of anaemia. Methods: We conducted a retrospective study from January 2011 to December 2012 in the internal medicine department of the Point "G" University Hospital. All hospitalised patients aged 65 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As discussed above, the substitution of A and X ions gives rise to anisotropic deformation of the crystal structure (Figure 1c). Therefore, the magnetic anisotropy J′/J also varies from 0.25 in CROC to 0.45 in Ba 3 ReO 5 Br 2 20 (Table 1). The change in magnetic ground state with magnetic anisotropy is also of interest.…”
Section: Discussionmentioning
confidence: 96%
“…As discussed above, the substitution of A and X ions gives rise to anisotropic deformation of the crystal structure (Figure 1c). Therefore, the magnetic anisotropy J′/J also varies from 0.25 in CROC to 0.45 in Ba 3 ReO 5 Br 2 20 (Table 1). The change in magnetic ground state with magnetic anisotropy is also of interest.…”
Section: Discussionmentioning
confidence: 96%
“…This artificial neuron can sense different pressures and convert them into spike trains, while also perceiving temperature through the metal-insulator transition of the material [100]. In addition, Han et al demonstrated a multimodal sensing device capable of simultaneously receiving visual and thermal stimulation signals [101]. Wang et al reported a multi-mode MXene-ZnO memristive device that simulates the unique environmental adaptation behavior of the human eye by combining light sensing and relative humidity sensing [102].…”
Section: Artificial Perceptionmentioning
confidence: 99%
“…It is worth noting that considering the raised float gate potential by the enhanced charge tunneling tends to further promote source injection, a positive feedback loop in Figure 3c would form and lead to the rapid charging of float gate and steep threshold switching behavior. Though positive feedback transistors had been previously designed for threshold switching by engineering the dopant profile in transistors, [33,34] the present device has a distinct float gate transistor configuration that stores memory states.…”
Section: Threshold Switching Mechanism Via Lateral Electric Field Acc...mentioning
confidence: 99%